Sistema de monitoreo y registro de máquinas de procesos industriales - Sequira-Cabrera, Enrique (Instituto Tecnológico de Costa Rica, 2000)
The industry works with different kinds of machines, some times this machines stops to receive maintenance. Almost every company has a statistics control of his production, this include the time that each machine works or stops to receive maintenance. Although, this statistics isn’t actualized continuously, this situation can produce a low quality product or a production retard. To solve this problem and has actual statistics of the state of each machine, a registry and monitor system was design and built. This system can communicate with a computer and show the information of each monitored machine. The designed circuit has a microcontroler, PIC16F877, to determinate the machine state function. To communicate the system with the computer, was utilized the industrial communication system called RS485. It was necessary to make a RS232- RS485 converter to communicate the PC with the designed system. The industrial communication system, RS485, can communicate over 1.2 Km and can have over 128 transmitters on bus. Software was made to take and show all the information of the function state of each machine.
Proyecto de Graduación (Bachillerato en Ingeniería Electrónica) Instituto Tecnológico de Costa Rica. Escuela de Ingeniería Electrónica, 2000.
Keywords: Microcontrolador; Software; Señales; Diseño; Comunicación; Información